Barriers and facilitators to incident reporting in mental healthcare settings: a qualitative study - Archer,S; Thibaut,B; Dewa,L; Ramtale,S; D'Lima,D; Simpson,A; Murray,K; Adam,S; Darzi,A (Journal of Psychiatric and Mental Health Nursing, 2020)
IntroductionBarriers and facilitators to incident reporting have been widely researched in general healthcare. However, it is unclear if the findings are applicable to mental healthcare where care is increasingly complex.AimTo investigate if barriers and facilitators affecting incident reporting in mental healthcare are consistent with factors identified in other healthcare settings.MethodData were collected from focus groups (n=8) with 52 members of staff from across [a large Mental Health] Trust and analysed with thematic analysis.ResultsFive themes were identified during the analysis. Three themes (i)learning and improvement, (ii)time, and (iii)fear were consistent with the existing wider literature on barriers and facilitators to incident reporting. Two further themes (iv)interaction between patient diagnosis and incidents and (v)aftermath of an incident – prosecution specifically linked to the provision of mental healthcare.ConclusionsWhilst some barriers and facilitators to incident reporting identified in other settings are also prevalent in the mental healthcare setting, the increased incidence of violent and aggressive behaviour within mental healthcare presents a unique challenge for incident reporting.Clinical ImplicationsAlthough Interventions to improve incident reporting may be adapted/adopted from other settings, there is a need to develop specific interventions to improve reporting of violent and aggressive incidents.